Dysregulation of NRF2 in cancer: From molecular mechanisms to therapeutic opportunities - Jung, Byung Jin; Yoo, Hwan Sic; Shin, Sooyoung; Park, Young Joon; Jeon, Sang Min (Biomolecules and Therapeutics, 2018)
Nuclear factor E2-related factor 2 (NRF2) plays an important role in redox metabolism and antioxidant defense. Under normal conditions, NRF2 proteins are maintained at very low levels because of their ubiquitination and proteasomal degradation via binding to the kelch‑like ECH associated protein 1 (KEAP1)-E3 ubiquitin ligase complex. However, oxidative and/or electrophilic stresses disrupt the KEAP1-NRF2 interaction, which leads to the accumulation and transactivation of NRF2. During recent decades, a growing body of evidence suggests that NRF2 is frequently activated in many types of cancer by multiple mechanisms, including the genetic mutations in the KEAP1-NRF2 pathway. This suggested that NRF2 inhibition is a promising strategy for cancer therapy. Recently, several NRF2 inhibitors have been reported with anti-tumor efficacy. Here, we review the mechanisms whereby NRF2 is dysregulated in cancer and its contribution to the tumor development and radiochemoresistance. In addition, among the NRF2 inhibitors reported so far, we summarize and discuss repurposed NRF2 inhibitors with their potential mechanisms and provide new insights to develop selective NRF2 inhibitors.
Keywords: Cancer; KEAP1; NRF2; NRF2 inhibitors